Pengaruh Keragaman Produk Dan Kepercayaan Terhadap Minat Beli Online Saat Pandemi Covid-19 - Melia Putri; Caska Caska; Hardisem Syabrus (Jurnal Dinamika Ekonomi & Bisnis, 2022)
This research was based on the decline in consumer buying interest during Covid-19 pandemic. This research aims to determine the influence of product diversity and trust toward online buying interest during the Covid-19 pandemic to FKIP Riau University students. The type of this research is correlational reseacrh with a quantitative approach. This research was conducted at the Faculty of Teacher Training and Education, Riau University with students from 2018, 2019, and 2020 batch being the population. This research used puposive sampling in determining the research sample. To interpreted the research results, the data analysis technique used is multiple linear regression. The result of this study found that product diversity and trust had a positive and significant effect on online buying interest with a significant level of 66.9%.